2018
DOI: 10.1261/rna.066589.118
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of 01/A′–A0 pre-rRNA processing by-product in human cells involves cooperative action of two nuclear exosome-associated nucleases: RRP6 and DIS3

Abstract: Pre-rRNA processing generates mature 18S, 5.8S, and 28S/25S rRNAs through multistage removal of surrounding 5 ′ ′ ′ ′ ′ -ETS/ 3 ′ ′ ′ ′ ′ -ETS and intervening ITS1/ITS2 segments. Endonucleolytic activities release by-products, which need to be eliminated. Here, we investigated the interplay of exosome-associated 3 ′ ′ ′ ′ ′ -5 ′ ′ ′ ′ ′ exonucleases DIS3 and RRP6 in rRNA processing and by-product elimination in human cells. In agreement with previous reports, we observed accumulation of 5.8S and 18S precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…Abbreviations: CH, ceratohyal; M, Meckel's cartilage. EXOSC3, EXOSC8, EXOSC9, EXOSC10, or DIS3 depletion causes the appearance of mis-processed 5.8S pre-rRNA species and accumulation of larger rRNA precursors (Tomecki et al, 2010;Lubas et al, 2011;Tafforeau et al, 2013;Sloan et al, 2013bSloan et al, , 2014Kobylecki et al, 2018;Davidson et al, 2019). Moreover, a recent study showed that neurological disease-associated mutations of EXOSC3 indeed caused pre-rRNA processing defects when introduced into Rrp40, the EXOSC3 homologue in budding yeast (Gillespie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: CH, ceratohyal; M, Meckel's cartilage. EXOSC3, EXOSC8, EXOSC9, EXOSC10, or DIS3 depletion causes the appearance of mis-processed 5.8S pre-rRNA species and accumulation of larger rRNA precursors (Tomecki et al, 2010;Lubas et al, 2011;Tafforeau et al, 2013;Sloan et al, 2013bSloan et al, , 2014Kobylecki et al, 2018;Davidson et al, 2019). Moreover, a recent study showed that neurological disease-associated mutations of EXOSC3 indeed caused pre-rRNA processing defects when introduced into Rrp40, the EXOSC3 homologue in budding yeast (Gillespie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…DIS3 was also found to be upregulated due to ER stress in Caenorhabditis elegans ( Sakaki et al, 2012 ), and we have found that TSC2-deficient neurons show evidence of ER stress ( Di Nardo et al, 2009 ). In addition, the RNA exosome complex is involved in ribosomal RNA maturation ( Kobyłecki et al, 2018 ; Pirouz et al, 2019 ), and mTORC1 is known to increase ribosomal biogenesis ( Gentilella et al, 2015 ). Therefore, it is possible that mTORC1 may induce the RNA exosome by stimulating the production of ribosomes, and the RNA decay phenomenon that we observe could be a side effect of this process.…”
Section: Discussionmentioning
confidence: 99%
“…DIS3 was also found to be upregulated due to ER stress in C. elegans (Sakaki et al, 2012), and we have found that TSC2-deficient neurons show evidence of ER stress (Di Nardo et al, 2009). In addition, the RNA exosome complex is involved in ribosomal RNA maturation (Kobylecki et al, 2018; Pirouz et al, 2019), and mTORC1 is known to increase ribosomal biogenesis (Gentilella et al, 2015). Therefore, it is possible that mTORC1 may induce the RNA exosome by stimulating the production of ribosomes, and the RNA decay phenomenon that we observe could be a side effect of this process.…”
Section: Discussionmentioning
confidence: 99%